Chemotherapy in the definitive management of oral cancers: Where do we stand today?. (March 2020) - Geiger, Jessica L.; Adelstein, David J.
Highlights: Primary surgical resection followed by appropriate adjuvant therapy remains the standard of care treatment for locoregionally advanced oral cavity cancer. The addition of high dose cisplatin to post-operative radiotherapy is indicated for patients with extranodal extension and/or positive surgical margins. There is no data demonstrating equivalent effectiveness for alternative dosing schedules or agents. Induction chemotherapy and/or definitive concurrent chemoradiotherapy are not recommended as standard treatments in locoregionally advanced oral cavity cancer. Abstract: The treatment of locally advanced oral cavity cancer is often multimodal, involving surgical resection, radiotherapy (RT), and chemotherapy. Systemic therapy is the mainstay of treatment for recurrent/metastatic disease. While the concurrent use of cisplatin with post-operative RT is well established in patients with high risk features of extranodal extension and/or positive surgical margins following resection, the role of chemotherapy in other curative settings is not clear. Studies reporting success of induction chemotherapy or definitive chemoradiotherapy in absence of primary resection include all anatomic sites of head and neck cancer, and oral cavity cancer subset is rarely reported as a separate analysis, thus limiting the interpretation of results. This article will focus on the use of systemic therapy for locoregionally advanced oral cavity cancer.